PERAN BIDANG PENGAWASAN ISI SIARAN KOMISI PENYIARAN INDONESIA DAERAH (KPID) BALI DI PROPINSI BALI - Sedia, I Wayan (Universitas Mahendradatta Denpasar, 2023)
Abstract- KPID is an institution assigned by the state to ensure that information conveyed by various media to the public can be received accurately according to the facts. The media as a communicator in conveying messages in the form of information conveyed to the public as communicants should contain information value that has a positive impact. Objectivity in reporting is a must for every media, both print and electronic media. The role of KPID in supervising broadcasting media is increasingly important in the tremendous current of globalization. In reality, a lot of incoming information is unstoppable, both having a negative impact and beneficial to the public and development as a whole. Television and radio are media that are still popular with rural communities, where the highest level of education is only high school. Such conditions are very easily dragged by various types of news. The tendency of the media in order to survive, often cooperates with capitalists and politicians, with a certain vision and mission, so that the news presented is often not objective and detrimental to the public. Key Word ; Control, KPI, Bali